Fulcrum of evil ISI-CIA-Al qaeda nexus - Dhar, Maloy Krishna (New Delhi, 2006)
The volume incorporates details of major Pakistani security and intelligence services, structural and functional characteristics of the ISI and its devastating interventions in the internal political affairs of Pakistan. The book delves deep into the ISI's intricate connectivity with the International Islamic Jihad movement.
Keywords: National security